PENERAPAN PERMAINAN INTERAKTIF UNTUK MENINGKATKAN MINAT BERBAHASA INGGRIS ANAK-ANAK DI YAYASAN RANGKUL PEDULI SESAMA - Ludovikus, Ludovikus; Mailintina, Yurita; Panjaitan, Ribka Sabarina; Supriyani, Nanik (Amare, 2024)
The implementation of this interactive game evaluates the impact of English learning activities at the Rangkul Peduli Sesama Foundation on children's understanding. This community service activity aims to create awareness and knowledge in children about how important English is for them in the future and increase children's motivation. This activity was attended by 30 children. Analysis of pre-test and post-test data showed a significant increase in their English knowledge after the learning activities. There was a substantial increase in minimum and maximum scores, with the mean score increasing from 59.40 to 88.26. A lower standard deviation in the post-test indicates uniform understanding of English among children. Creative and innovative learning methods, including the use of interactive games, have proven effective in increasing children's interest and understanding of English from 4 to 14 years old. Post-activity evaluations and attention to health and safety, especially in a global pandemic, are also taken into account. This activity confirms that learning is successful in significantly improving children's understanding of English, providing a strong foundation for the development of English language skills in the future.